Crystallographic texture evolution in electron beam melting additive manufacturing of pure Molybdenum. (September 2021) - Fernandez-Zelaia, Patxi; Ledford, Christopher; Ellis, Elizabeth A.I.; Campbell, Quinn; Rossy, Andrés Márquez; Leonard, Donovan N.; Kirka, Michael M.
Graphical abstract: Highlights: Crack-free pure molybdenum is fabricated via electron beam melting AM. Fiber texture switching is observed across various energy density settings. The weld pool shape likely drives the fiber selection mechanism. Columnar grains consist of fine subgrains believed to be due to process stresses. Abstract: Additive manufacturing (AM) technologies offer novel opportunities for processing difficult to cast refractory materials. Electron beam melting (EBM) AM is particularly attractive as the rapidly moving electron beam can be utilized to heat the powder bed which mitigates against some process induced cracking mechanisms. A great deal of prior work has been done to investigate laser based processing of molybdenum but little EBM focused work currently exists. In this work we investigate EBM processed molybdenum and observe sharp 0 0 1, 1 1 1, and mixed 0 0 1 & 1 1 1 crystallographic fibers in the build direction. The apparent preference between these build direction fibers is dependent on the imposed energy density and this is likely explained by the weld pool shape. Detailed microscopy reveals that the observed columnar grains consist of much finer equiaxed low angle boundary subgrains suggesting large process induced stresses leading to appreciable plastic deformation. The implications resulting from this work are that molybdenum may be processed crack-free via EBM AM and that fiber-switching may be controlled, and exploited, towards fabricating components with optimized performance.